Estudio económico financiero al segmento de los comerciantes minoristas formales y su incidencia en la renta de las familias del cantón Quevedo, año 2012 - Cano Wong, Patricia Silvana (2013)
The investigation was realized between December, 2012 and March, 2013, in the Canton Quevedo, Province of The Rivers, one did it in order to analyze the economic financial situation of the formal retailers of this city, by means of surveys realized to the small businessmen affiliated to the Chamber of Trade, it was possible to clear several doubts that were had it brings over of the topic to investigating, beside knowing the situation of the merchants with regard to his income and expenses. By means of the survey it was possible to state that the majority of the retailers have top title, but that in spite of it are not totally qualified to administer his business, the majority of they they support debts with private banks and suppliers, it is for this that of his monthly income they occupy from 30 % to 60 % to pay his debts. Likewise they have problems that they affect directly to his business since it is the lack of training to his employees since this has provoked that the formal retailers of the Canton Quevedo are in an economic stagnation. The analysis and interpretation of the results of the surveys, it allowed to know that the small businessmen of this canton are in an economic stagnation due to the bad administration in his business, provoking economic and financial problems that concern the revenue of his families. It is important that the merchants support an obligatory training brings over of the managing of his resources, this is a work for the Chamber of Trade, in which there are taught they brings over of business administration, training and preparation of the personnel, administration of his financial resources, between others.